Kekuasaan Biopolitik Negara dalam Novel Pengacara Jalanan Karya John Grisham: Kritik Homo Sacer Giorgio Agamben - Valentina Edellwiz Edwar; M Alfian (Balai Bahasa Sulawesi Selatan, 2023)
This research reveals the american state's political strategy in managing the law for citizens, as well as citizen resistance in the American political and legal space in Pengacara Jalanan. The research question asked is (1) what is the life form of homeless politically and legally?; and (2) how does homelessness act to save his life in the political and legal space of the country? This problem of biopolitic space (politics and law) was analyzed using Giorgio Agamben's theory of political philosophy manifested in the concepts of sovereign power, bare life, and homo sacer. The research method used is qualitative descriptive. Data is collected through library studies and listening techniques. Data analysis is carried out by content analysis: data reduction, data classification, and data analysis. The results of the study are (1) homeless life experiences ambivalence because it is inside the legal space of the country, as well as being outside the state law because of the impact of political suspension of the law. The ambivalent life of homelessness results in the death of homelessness as a legal-juridical prevalence; (2) The act of homelessness to obtain a happy form of life is realized by moderate actions and radical actions, both of which are faced with sovereign power. John Grisham's novel Pengacara Jalanan is a representative critique of America's democratic pattern of governing the social body and political body of its citizens.